Les phalanges des mains sont-elles un bon indicateur de l’âge au décès des adultes ? - Aurore Schmitt (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Phalanges of the hand, observed on X-rays, have been proposed as indicative of age at death of adults. The present study proposes testing the performance of this indicator on an identified osteological sample from the collection housed in the University of Coimbra (Portugal). A part of the sample was used as the reference population (n = 98) and the other part as a target series (n = 25). The relation between age at death and modifications of the phalanges was revealed to be unreliable. The difference between the results of our study and those of previous studies of this indicator is partly related to the nature of the samples studied.